Ex vivo and in vitro investigations on the protective effects of Combretum glutinosum Perr. ex DC against oxidative and inflammatory stress-induced liver and kidney damage - Mabozou Kpemissi; Dzidzoe Degbe; Abide Noelie Adjome; Kwashie Eklu-Gadegbeku (Elsevier, 2023)
Background: Organ damage, such as liver and kidney injury, is a serious and frequent problem leading to end-stage failure. Despite advances in research, there is still no proof of the effectiveness of potentially anti-inflammatory, antioxidant, and organoprotective compounds in therapeutic contexts. The need for potential therapeutic drugs is therefore enormous and urgent. For a long time, plant-based remedies, including Combretum glutinosum, have been a crucial component of healthcare. Methods: In order to develop anti-inflammatory, antioxidant, and organoprotective phytomedicine, the current research aims to evaluate the nephroprotective and hepatoprotective abilities of C. glutinosum extract, targeting its anti-inflammatory and antioxidant potential using ex vivo and In vitro models. Results: The phytochemical screening pointed out a large number of beneficial substances, including flavonoids, tannins, polyphenols, alkaloids, and terpenoids. C. glutinosum extract showed strong anti-inflammatory activity against heat and hypotonia-induced protein denaturation and membrane destabilization. Moreover, remarkable antioxidant action in DPPH radicals, ferric-reducing antioxidant power (FRAP), and Total Antioxidant Capacity (TAC) Ferric chloride/ascorbic acid (FeCl2-AA)-mediated lipid peroxidation in liver and kidney tissues was significantly (p < 0.001) mitigated by C. glutinosum extract. Conclusion: C. glutinosum has a good anti-inflammatory and antioxidant profile. This would place it among the potential candidates for hepatoprotective and nephroprotective activities.